Identifying the relationship between preparatory mechanics and an athletes risk of acl injury: a preliminary analysis - Staynor, J.; Alderson, J.; Reinbolt, J.; Donnelly, C. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
This study investigated whether an athlete's mechanics during the preparatory phase of unplanned sidestepping predicted peak valgus knee moments during weight acceptance. Nine female community level team sport athletes completed an established sidestepping movement assessment. Preparatory anterior-posterior trunk momentum and left-right lateral trunk momentum, alongside trunk flexion range of motion during weight acceptance combined to predict 57% of the variance in peak knee valgus moments. These preliminary results show that preparatory trunk mechanics are related to subsequent peak knee valgus moments and anterior cruciate ligament injury risk during unplanned sidestepping. A data set of 116 mixed characteristic athletes is currently being analysed to verify these findings.